Peran Mediasi Job Satisfaction dan Employee Engagement Pada Compensation Terhadap Job Performance Di PT Telkom Indonesia Regional Jabodetabek Banten - Auzan Hilman Hustanto; Indah Lestari; Syilvia Anggraini; Andre Kurnia Ramadhan; Andreas Wahyu Gunawan Putra (Jurnal Manajemen, 2021)
During the technological era, it had many impacts on various industries in Indonesia, one of which was the telecommunications industry which experienced a drastic increase in customer demand due to work from home instructions that could make working from anywhere so that discussions and giving work orders were not limited by space and time. This makes working hours longer and erratic, causing changes to routines and causing job performance to be disrupted, so an appropriate compensation strategy is needed by taking into account job satisfaction and employee engagement. Therefore, it is interesting to study how these factors affect job performance. This study aims to examine the effect of compensation given by the company on job performance mediated by job satisfaction and employee engagement. This research is a quantitative research with random sampling which involved 187 employees of PT Telkom Indonesia Regional Jabodetabek Banten. The analytical tool in this study uses SEM-PLS. The results of the study have novelty, namely compensation does not have a direct significant effect on job performance, but can be through employee engagement mediation. In addition, this study shows that job satisfaction has no significant effect on job performance either directly or as a mediating variable. The implication for the company is to know the importance of increasing compensation through employee engagement to improve job performance. From the results of the study, it is recommended to study more deeply related to other factors that affect job performance in other industries Keyword: Compensation, Job satisfaction, Employee Engagement, Job Performance